PENYEBAB DAN TATALAKSANA DALAM MENGATASI KELOID - Dea Amelia Glorie; Wiwi Kertadjaya; Reni Angeline (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Pathological wound healing and pathological scar formation lead to functional and aesthetic losses. Keloids are excessive scars that grow beyond the boundaries of the original wound which is a fibroproliferative disorder. Keloids are difficult to treat because of the recurring nature of keloids and imperfect treatment of keloids can make keloids worse. Based on this description, this literature review was created by the author to explain the causes and treatments for keloid. The research articles reviewed are in the form of analytical reviews through the PubMed database. A total of 20 research articles were selected according to the purpose of writing this literature review. The main cause of keloids is trauma, injury or infection of the skin. Monotherapy for keloids isn’t recommended because of the higher recurrence rate compared to combination therapy. Several modalities for the treatment of keloids are surgical procedures, radiotherapy, antitumor/anticancer, calcium electroporation, corticosteroids, intermittent magnetic pressure, silicone gel, laser, Plasma Skin Regeneration, and cryotherapy. Excision is a modality that provides instant reduction in keloid size, but due to the high recurrence, other therapies must be given as combination therapy, namely corticosteroid injections or radiotherapy, which can reduce the recurrence rate after excision.